The Role of Translanguaging in Enhancing Students’ Enthusiasm in Mu’askar Lughoh: A Linguistic–Psychological Study: Peran Translanguaging dalam Meningkatkan Antusiasme Siswa dalam Mu’askar Lughoh: Studi Linguistik-Psikologis - Luluk Yuliani; Icha Gilang Permata (Language Development Center, 2025)
Background: One of the activities that supports Arabic language learning is Mu’askar Lughoh, which applies a translanguaging approach. From both linguistic and psychological perspectives, this approach is considered capable of increasing students’ enthusiasm for learning Arabic. Purpose: This study aims to further explore the translanguaging from a linguistic perspective, translanguaging from a psychological perspective, and assess students’ level of enthusiasm. Method: This research employs a mixed-methods design. Data were collected through interviews, questionnaires, and documentation involving 43 Arabic Language Education students at UIN Sayyid Ali Rahmatullah Tulungagung. The sampling technique used was non-probability sampling with a purposive sampling type. The data were analyzed using Miles and Huberman’s framework along with descriptive statistical analysis. Results and Discussion: From a linguistic perspective, the application of translanguaging helped students understand the material more comprehensively. From a psychological perspective, translanguaging positively contributes to increasing students’ self-confidence and willingness to communicate in Arabic, which in turn fostered greater enthusiasm for participating in Mu’askar Lughoh. The mean level of students’ enthusiasm is 89,93 with a standard deviation of 11.95, which falls into the moderate category. Conclusions and Implications: Application of translanguaging in Mu’askar Lughoh holds significant potential for developing students’ Arabic language proficiency. The organizers of Mu’askar Lughoh can use the research results as evaluation material to boost students’ enthusiasm by reviewing and improving the curriculum, teaching strategies, learning facilities, and non-formal activities. Further research could examine the effectiveness of translanguaging through a longitudinal approach and broaden the analysis to include cultural and social factors that may influence the program’s success, thereby further enhancing student enthusiasm.